The redox rhythm gates immune-induced cell death distinctly from the genetic clock - Sargis Karapetyan; Musoki Mwimba; Tianyuan Chen; Zhujun Yao; Xinnian Dong (Proceedings of the National Academy of Sciences, 2025)
Organisms use circadian clocks to synchronize physiological processes to anticipate the Earth’s day-night cycles and regulate responses to environmental signals to gain competitive advantage. While divergent genetic clocks have been studied extensively in bacteria, fungi, plants, and animals, an ancient conserved circadian redox rhythm has been recently reported. However, its biological function and physiological outputs remain elusive. Here, we uncovered the coexistence of redox and genetic rhythms with distinct period lengths and transcriptional targets through concurrent metabolic and transcriptional time-course measurements in an Arabidopsis long-period clock mutant. Analysis of the target genes indicated regulation of the immune-induced programmed cell death (PCD) by the redox rhythm. Moreover, this time-of-day-sensitive PCD was eliminated by redox perturbations and by blocking the signaling pathway of the plant defense hormones jasmonic acid/ethylene, while remaining intact in genetic clock-defective backgrounds. This study shows that compared to robust genetic clocks, the more sensitive circadian redox rhythm serves as a signaling hub in regulating incidental energy-intensive processes, such as immune-induced PCD involving reprogramming of chloroplast and mitochondria activities, to provide organisms a flexible strategy to mitigate metabolic overload during stress responses.